2004
DOI: 10.1037/0735-7044.118.5.1123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise on Pavlovian Fear Conditioning.

Abstract: Exercise promotes multiple changes in hippocampal morphology and should, as a result, alter behavioral function. The present experiment investigated the effect of exercise on learning using contextual and auditory Pavlovian fear conditioning. Rats remained inactive or voluntarily exercised (VX) for 30 days, after which they received auditory-cued fear conditioning. Twenty-four hours later, rats were tested for learning of the contextual and auditory conditional responses. No differences in freezing behavior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
47
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 36 publications
8
47
1
Order By: Relevance
“…6A). These data suggest that unlike chronic wheel running which has been reported to have no effect on the acquisition of auditory fear conditioning (Baruch et al 2004), brief access to running wheels could interfere with auditory fear conditioning learning. One wheel did not record running distance during the wheel running familiarization period, so this rat was omitted from this correlational analysis.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…6A). These data suggest that unlike chronic wheel running which has been reported to have no effect on the acquisition of auditory fear conditioning (Baruch et al 2004), brief access to running wheels could interfere with auditory fear conditioning learning. One wheel did not record running distance during the wheel running familiarization period, so this rat was omitted from this correlational analysis.…”
Section: Resultsmentioning
confidence: 72%
“…While short-term exercise has profound effects on the hippocampus (Neeper et al 1995(Neeper et al , 1996Molteni et al 2002), a structure important for contextual fear conditioning (Rudy et al 2002;Matus-Amat et al 2004;Chang and Liang 2016), less is known regarding exercise effects on the amygdala, a region critical for the CS-US association formed during auditory fear conditioning (Huff and Rudy 2004;Bergstrom 2016). Moreover, the effects of exercise on auditory fear conditioning are not as well characterized as contextual fear conditioning (Baruch et al 2004;Falls et al 2010). To our knowledge, no prior research has investigated effects of only a few days of wheel running on auditory fear conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, running again interacted with the nature of the learning experience; distance covered in the run after the extended nonshocked exposure was negatively correlated with the test levels of freezing; distance covered in the run after the brief nonshocked exposure was positively correlated with the test levels of freezing. Previous studies have shown that rodents provided with access to wheels for several weeks prior to contextual fear conditioning exhibit more freezing than sedentary controls when subsequently tested in that context (Baruch et al 2004;Clark et al 2008). This increased freezing has been found when access to the wheels continued across the subsequent tests and when that access was terminated prior to testing, suggesting that the history of exercise before conditioning was sufficient for the increased levels of freezing across subsequent testing.…”
Section: Discussionmentioning
confidence: 99%
“…One of the variables that influence the acquisition of conditioned fear in rodents is a history of exercise. Rodents provided with access to running wheels for several weeks and then shocked in a distinctive context exhibit more fear (typically freezing responses) than sedentary controls (Baruch et al 2004;Burghardt et al 2004Burghardt et al , 2006Van Hoomissen et al 2004;Clark et al 2008;Kohman et al 2011). This increase in conditioned fear is consistent with running-induced improvements in learning and memory found in other tasks, such as the Morris water maze (O'Callaghan et al 2007; Gomes da Silva et al 2012).…”
mentioning
confidence: 99%
“…Although there are many similarities between cued and contextual fear conditioning, such as experience of the footshock, exposure to the tone and to the conditioning context, there are also differences in associations learned and brain regions involved. For example, entorhinal lesions or lesions of the bed nucleus of the stria terminalis have little effect on conditioned responding to discrete cues, but diminish responding to contextual cues (Sullivan et al, 2004, Majchrzak et al, 2006, while voluntary exercise improves conditioned responding to contextual, but not discrete conditioned stimuli (Baruch et al, 2004). Conversely, lesions of the nucleus accumbens core have no effect on responding to the contextual cues, but disrupt conditioned responding to the tone CS (Cassaday et al, 2005).…”
Section: Discussionmentioning
confidence: 96%